Papieska Rada ds. Tekstów Prawnych wobec wątpliwości związanych z Listem apostolskim „Mitis Iudex Dominus Iesus” - Gałkowski, Tomasz (Ius Matrimoniale, 2016)
The subject of the study is the analysis of the content of specific answers which were given by the Pontifical Council for Legislative Texts with regard to doubts which arose after the promulgation of the Apostolic Letter„Mitis Iudex Dominus Iesus”. Some of them were published on the website of the Council, others on the websites of Italian Bishops` Conference and other sites dedicated to canon law. Some answers were placed there as explanatory notes. Therefore, it was necessary to explain the difference between declarations, explanatory notes and specific answers to next comment on answers.